A representação poética do negro e sua cultura em Urucungo de Raul Bopp - Araújo, José Helber Tavares de (2008)
This research constitutes a study of poems about black representation in Urucungo (1932), by Raul Bopp, a work which is strongly characterized by the principles of the modernist anthropophagic movement (Antropofagia). Considering this perspective, the purpose is to examine in what ways black people are represented in these poems, having two parameters as a basis: the use of Afro-Brazilian cultural elements and aspects concerning the social and historical process of black people as slaves. Following the dynamics inherent to literary studies, the analysis of poems emphasizes aesthetic construction, without ignoring historical components that play a relevant function in the text.